2023
DOI: 10.1007/s00198-023-06863-y
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of anti-fracture effectiveness of zoledronate, ibandronate and alendronate versus denosumab in a registry-based cohort study

Abstract: Summary This registry-based study of 3068 patients with osteoporosis compared the anti-fracture effectiveness of denosumab versus bisphosphonates. Denosumab was associated with significantly greater risk reduction than alendronate or ibandronate for vertebral and any fractures. No difference in fracture risk reduction was found between zoledronate and denosumab. Purpose To analyse the fracture risk of patients with osteoporosis receiving bisphosphonates or denosumab in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Alendronate (ALN) is a representative drug of the third generation of bisphosphonates 37 . Compared with the first two generations of drugs, it has stronger anti-bone resorption and no bone mineralization inhibition 38 . Zhou et al 39 observed that in C57BL mice, the use of alendronate alone can significantly increase serum glucagon-like peptide-1 levels compared with the diabetes group.…”
Section: Discussionmentioning
confidence: 99%
“…Alendronate (ALN) is a representative drug of the third generation of bisphosphonates 37 . Compared with the first two generations of drugs, it has stronger anti-bone resorption and no bone mineralization inhibition 38 . Zhou et al 39 observed that in C57BL mice, the use of alendronate alone can significantly increase serum glucagon-like peptide-1 levels compared with the diabetes group.…”
Section: Discussionmentioning
confidence: 99%
“…This registry consecutively enrols subjects referred for a dual-energy X-ray absorptiometry (DXA) scan, and to date, three outpatient centres in Bern, Zurich, and Lucerne include patients undergoing romosozumab therapy. Previously described variables are assessed for each patient [12][13][14], and additional data are collected for patients receiving romosozumab, including cardiovascular risk factors and outcomes. The primary objective of this initial analysis was to identify predictive factors, in particular prior therapies, for changes in BMD after 12 months of therapy with romosozumab.…”
Section: Setting and Outcomementioning
confidence: 99%
“…However, it was shown that high doses of RANKL inhibitors can transform accumulating osteomorphs into active osteoclasts that lead to bone resorption, which is accompanied by fractures [136]. The effectiveness of denosumab has been studied in comparison with bisphosphonates and found that it was associated with a significantly greater reduction in the risk of vertebral and other fractures than alendronate or ibandronate, but no differences were found compared with zoledronate [153]. Clinical studies have shown that long-term therapy with denosumab for up to 10 years was associated with an increase in bone mineral density (BMD), a low incidence of fractures, and a low level of side effects [154].…”
Section: Rankl Inhibitorsmentioning
confidence: 99%